2011
DOI: 10.1098/rsbl.2010.1180
|View full text |Cite
|
Sign up to set email alerts
|

Individuality in bird migration: routes and timing

Abstract: The exploration of animal migration has entered a new era with individual-based tracking during multiple years. Here, we investigated repeated migratory journeys of a long-distance migrating bird, the marsh harrier Circus aeruginosus, in order to analyse the variation within and between individuals with respect to routes and timing. We found that there was a stronger individual repeatability in time than in space. Thus, the annual timing of migration varied much less between repeated journeys of the same indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
154
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(164 citation statements)
references
References 26 publications
9
154
1
Order By: Relevance
“…Repeated measures of single individuals can also provide fundamental cues to understanding the causes of variability in migratory behaviour (for example, the relative role of genetic background versus environmental conditions; van Noordwijk et al 2006), and also to unveil the mechanisms underlying long-distance navigation (Alerstam 2006;Guilford et al 2011). By repeatedly tracking individual birds it was possible, for example, to show that (at least some) terrestrial long-distance migrants do not rely on learned visual maps of landscape features for most of the journeys to and from the wintering areas (Vardanis et al 2011).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Repeated measures of single individuals can also provide fundamental cues to understanding the causes of variability in migratory behaviour (for example, the relative role of genetic background versus environmental conditions; van Noordwijk et al 2006), and also to unveil the mechanisms underlying long-distance navigation (Alerstam 2006;Guilford et al 2011). By repeatedly tracking individual birds it was possible, for example, to show that (at least some) terrestrial long-distance migrants do not rely on learned visual maps of landscape features for most of the journeys to and from the wintering areas (Vardanis et al 2011).…”
mentioning
confidence: 99%
“…Some species are clearly more faithful than others to their wintering sites, routes, stopovers and timings (Sutherland 1998;Catry et al 2004). Most studies carried out so far on fidelity to migratory paths and stopovers have focused on species that migrate mostly over land, such as passerines, storks, geese and raptors (Fox et al 2002;Berthold et al 2004;Catry et al 2004;Alerstam et al 2006;Vardanis et al 2011;Stanley et al 2012). While some studies have analysed spatial consistency during migration in pelagic travellers (Hunter et al 2003;Phillips et al 2005;Broderick et al 2007;Guilford et al 2011), none have attempted to disentangle the fidelity to routes or paths from individual consistency in winter destinations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Such behavioural adjustments, by learning from individual experience or by observing others, can happen relatively quickly [29,30]. It has been previously shown that birds, including soaring raptors, have high phenotypic plasticity of migratory routes [31,32]. However, it remains unclear whether Oriental honey-buzzards have the necessary adaptive potential relative to the speed of climate change.…”
Section: (A) Mid-century Conditionsmentioning
confidence: 99%